Pengaruh Etika Bisnis Islam, Kualitas Pelayanan dan Nilai Taksiran Terhadap Minat Nasabah Menggunakan Layanan Gadai Mas SulSel Cabang Gowa - Risma, Risma; Faturrahman, Faturrahman; Sofyan, A.Syathir (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
This research aims to determine the influence of Islamic business ethics, service quality and estimated value on customers' interest in using the Gowa Branch of the Mas SulSel pawn service, where the sample in this study is customers who use the Gowa branch of the Mas SulSel pawn service. The method used in this research is a quantitative method with a descriptive approach. Based on the research results, it was found that the first hypothesis was accepted, namely that Islamic business ethics had a positive and significant effect on customers' interest in using the Gowa branch of the Mas South Sulawesi pawn service. Likewise, the second and third hypotheses are also accepted, where service quality and estimated value have a positive and significant effect on customer interest in using the Gowa branch of the Mas South Sulawesi pawn service. And with that, the fourth hypothesis is also accepted, where the three variables, namely Islamic business ethics, service quality and estimated value simultaneously influence customer interest in using the Gowa branch of the Mas South Sulawesi pawn service.